A new method to evaluate the performance of slime water treatment. Issue 6 (18th March 2016) - Xu, H. X.; Cheng, G.
ABSTRACT: Slime water is used repeatedly and its treatment is very essential in coal preparation plants. A new method called fractal dimension is proposed to evaluate the performance of slime water treatment. According to settling experiments, the settling process of slime water can be divided into two phases. In the first phase, water hardness is less than 50 DH° and settling velocity is fast. In the second phase, the water hardness is over 50 DH° and settling velocity is slow. Under different water hardness levels, the variation trends of the luminosity of the supernatant liquor, settling velocity, and fractal dimensions are consistent.